Genótipos de tomateiros infectados por patógenos e tratados com medicamentos homeopáticos: severidade de doenças e aspectos fisiológicos - Toledo, Márcia Vargas (2014)
The current agricultural model is based on the use of xenobiotics, with consequences that must be counted, among them are the genetic erosion, pollution by the abusive use of pesticides and fertilizers, food contamination, increase of pests, diseases and weeds. Researchers have turned to the development of more sustainable technologies, which cause less environmental impact, such as the alternative control of pest insects and plant pathogens. The tomato (Solanum lycopersicum L.) is one of the most consumed vegetables in the country, it is subjected to the attack of many pests and diseases and because of this, one of the most contaminated by pesticides, thus the study of alternative forms of control is an important area to be developed. The homeopathic is a science that can provide a more sustainable agriculture, it is of low cost and environmentally correct. The aim of this study was to cooperate to the development of alternative methods of diseases control and generate knowledge to contribute to the strengthening and consolidation of the homeopathic science. It was developed in three phases, the first chapter on the study of the fungitoxic action of the homeopathic medicines Sulphur, Ferrum sulphuricum and Propolis against Alternaria solani, causal agent of early blight in tomato; the second concerning the homeopathic action of Ferrum sulphuricum in controlling the powdery mildew disease caused by a biotrophic fungus, the Oidium neolycopersici, and also the response of two tomato genotypes regarding the genetic improvement intensity. On the third chapter physiological aspects of two hemibiotrophic pathogens interaction, A. solani and Stemphylium solani were studied in tomato treated with Sulphur, Ferrum sulphuricum and Propolis. Data showed that drugs have activity on tomato diseases control by direct action on the pathogen, and also on the host, by the resistance induction and the increase of growth variables. It was also found that species which have been more genetically improved respond less to homeopathy. The results confirm the homeopathy potential on the control of diseases as well as on the generation and maintenance of plants health